Blazing earth - Brisbin, Terri (Brisbin, Terri. Novel of the stone circles., 2016)
In the new Novel of the Stone Circles by the USA Today bestselling author of Raging Sea, the ancient and wrathful goddess of fire plots her escape as the future depends on the untapped powers of two lovers. Tolan of Durlington is a farmer whose ancestors have tended the same lands for centuries with astonishing success. His hope for the future is that his son and his sons yet to come will carry on the traditions. But, his carefully laid plans are shaken by the village healer he's come to love. Unable to bear children, Elethea can offer Tolan only companionship and physical comfort. When hidden powers in their blood- powers to command the fertile earth, to draw from the healing sun- explode into being, their world and lives are changed forever. Soon, the fate of humankind is in their hands as the wrathful goddess grows closer to escaping her prison and destroying the world as they know it. Battling the goddess followers and their own fears, can these two lovers protect mankind and still survive to find their own future?